The Impact of Volcanic Eruptions on Mental Health: A Narrative Review - Afifah Cahya Imani Arifin; BS. Titi Haerana; Ratna Sari Dewi; Reski Ihsan Humang (Miracle Journal of Public Health, 2022)
Natural disasters such as volcanic eruptions are difficult to avoid and difficult to predict when they will occur. These events not only cause material, physical, economic and environmental losses, they can even affect a person's mental health. This study aims to determine the impact of a volcanic eruption disaster on mental health. The research method used is narrative review. The search for journals and articles is done through the Google Scholar database. Journals were selected based on the desired criteria, namely the impact of a volcanic eruption on mental health. The results of a narrative review of 7 related literature show that the majority of survivors of the volcanic eruption who experienced post-disaster trauma are women in the adult and elderly age categories. Disaster areas with high exposure or near volcanic areas have a higher risk of trauma, anxiety and mental stress than areas with low exposure. Symptoms of Post-Traumatic Stress Disorder (PTSD) can last for years or even decades. The mental stress and psychological morbidity experienced by survivors will decrease over time. Provide cognitive intervention which is one effective way to deal with anxiety.